Leadership Differences: Internationalization, Size and Development - Ivan Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Successful leadership is one of the most important factors contributing to the company's success, and can be defined in several ways that will be mentioned below. Leadership can be defined as the skill to encourage employees to voluntarily participate in the realization of the objectives of the company. Leadership is important for all groups of companies. Although the leadership in most of the cases represents the characteristics of leader, there are still specifics that are important to certain groups of companies. This paper will expose the reflections, as well as previous studies related to the specifics of leadership with regard to international orientation, stage of development and size of business.
Keywords: M1; F53; 330; leadership; internationalization; size; development